KETERAMPILAN MENULIS TEGAK BERSAMBUNG dan MEDIA ALFABET “SENYAWA” - Trimayasari, Kundarti (Universitas Muhammadiyah Magelang, 2016)
The purpose of this study was to determine the effect of the alphabet media “ SENYAWA “ to the improvement of writingskills continued straight grade II SD N Karangmulyo , Kab . Purworejo. This study approach used true experimentalresearch. Pretest posttest control group used as research design. Treatment arrange on 8 meetings , each meeting consist of thealphabet using the media “ SENYAWA “. The subjects of this study were 30 students who were divided into 2 groups: theexperimental group and the control group.The data collection technique used writing skills observation. Data were analyzed using T test. The study results showed thatthe media alphabet “ SENYAWA” had positive effect on students’ writing skills upright continued . Based on the test resultstwo groups conducted by the authors, obtained t < t table is -5.435 < 2.0484 and the average value of the experimentalgroup in the amount of 8.46 with a percentage of 39.2 % . These results indicate that the writing skills upright concatenatedexperimental group is higher than the control group